Challenges of Studying Management During Covid-19: A Student Perspective - Asti Nur Aryanti; Ayu Krishna Yuliawati (CV. AFDIFAL MAJU BERKAH, 2022)
The global pandemic of COVID-19 has caught many organizations changed the way organizations conduct their activities. Universities are learning organizations delivering knowledge to students. In a matter of days, the learning activities were changed into online mode after a brief announcement by the national government declaring a state of disaster in Indonesia. Online platforms in universities are common as most universities already conduct some form of online learning. But this time it was different. The pandemic has caused a barrier in a form of social distance, online. This study tries to answer the following questions: what are the students' perception of online learning in management programs? What challenges do the students face in online learning during COVID19, and what are the solutions for those challenges? Descriptive survey method was conducted on a sample of management students at several universities in Bandung. Questionnaires were distributed through an online platform with a snowball sampling technique. The results of this study indicate that students are not ready to follow the online learning system. Limited facilities, level of understanding, difficulty interacting with lecturers or fellow students, miscommunication due to misperceptions, unsupportive online learning environment, and technical problems become obstacles in online learning. Students prefer face-to-face learning over online learning. In essence, they are easier to grasp the material presented. In the teaching materials dimensions, respondents gave a negative response to all indicators, where the biggest negative 92% response was on the online college environment indicator.Then on the learning interaction dimension, the biggest negative response is 86% about online learning interactions with fellow students Furthermore, in the learning environment dimension, 94% of respondents stated th at they prefer face-to-face learning which provides convenience in solving problems